The effect of organizational commitment towards employees’ Islamic performance - Soraya Rizky Widyanti, Ari Prasetyo, (Opción, 2020)
Working is not only to fulfill the necessity of life, but it should be carried out in a proportional, progressive, procedural, and prompt manner. The research results suggested that organizational commitment has a positive and significant affected the employees’ Islamic performance. According to the results of the F test and t-test, the F statistics reached 8.059, and the t statistics amounted to 2.917, with a significant level of 0.005 for each test. It suggested that both had significant values of less than 0.05. This finding suggested that the organizational commitment significantly affected employee’s Islamic performance, both simultaneously and partially.